(untitled) (Research, Society and Development, 2022)
Cardiovascular diseases are among the most complex comorbidities associated with a worse prognosis for COVID-19 infection. Patients who have cardiac risk factors, such as the elderly, hypertensive and diabetic patients, seem to be more likely to acquire COVID-19, and may demonstrate increased severity and possible sequelae. This study aims to expose, through the analysis of scientific articles, the correlation between SARS-CoV-2 infection and pathologies of the cardiovascular system. This is a systematic qualitative literature review, carried out between 2019 and 2021 in Portuguese, English and Spanish. The results of this study can significantly contribute to the performance of health professionals, in general, evidencing the high morbidity and mortality rates of COVID-19 in individuals with some type of cardiovascular problem. The main fatal outcomes show that prevention measures must be better planned, considering the reality of heart diseases in Brazil, and that clinical situations are conducted rigorously, in addition to promoting data for updating protocols that reduce the number of cases that evolve to death. In general, all individuals who have COVID-19 infection can develop heart involvement, as a result of inflammatory responses, a history of other chronic diseases and biochemical disorders. More studies are needed to clearly elucidate the correlation between heart disease and SARS-CoV-2 infection, requiring the development of more specific research and protocols for the management of patients with cardiovascular diseases.